Internal Marketing and Anti-Productive Work Behaviors (Relationship and Effect): An Applied Study at Taif University - Alqutub, Kholoud Ragheb (Journal of Economic, Administrative and Legal Sciences, 2024)
This research aims to explore the extent to which there is a relationship and effect between internal marketing policies within educational organizations and anti-productive work behaviors among the employees, which helps forming the principles of internal marketing and anti-productive work behaviours within a systematic framework. This will assist the university management to develop training programs which contribute to work development and achieve the aimed results for this educational service. The research followed the quantitative method. This research was applied to administrative staff at Taif University, and questionnaires were used for primary data collection. The number of valid questionnaires was 204, which were analyzed using the SPSS statistical program. The most important recommendation suggests that it is necessary to adopt a clear policy for incentives and rewards, define and clarify the tasks and responsibilities of each member of staff and within the university, and pay more attention to training employees as well as achieving justice among them, especially regarding training opportunities.
Keywords: Internal Marketing; Counterproductive Behaviors; Internal customers; External customers